Prevalence of intestinal parasites and associated factors among food handlers in food establishments in the Lideta subcity of Addis Ababa, Ethiopia: an institution-based, cross-sectional study - Zemichael Gizaw; Woinishet Abera; Binyam Gintamo; Tewoderos Shitemaw; Zelalem Negash Mekuria (BMJ Open)
Objective This study was conducted to assess the prevalence of intestinal parasites and the associated factors among food handlers in the Lideta subcity of Addis Ababa, Ethiopia.Design An institution-based, cross-sectional study design was used. Stool samples were collected from food handlers and examined using direct wet mount and formalin-ether concentration techniques. Personal and establishment-related information was collected using a pretested questionnaire, with a structured observation. Multivariable binary logistic regression was used to identify factors associated with the prevalence of intestinal parasites on the basis of adjusted OR (AOR) and 95% CI and p values <0.05.Setting Food establishments in the Lideta subcity of Addis Ababa, Ethiopia.Participants 411 food handlers participated in the study.Outcome measures The primary outcome was the prevalence of intestinal parasites, defined as the presence of one or more intestinal parasitic species in stool samples.Results One or more intestinal parasites were detected in 171 (41.6%; 95% CI 36.6% to 46.4%) stool samples. The most common intestinal parasites were Entamoeba histolytica/dispar (12.7%), Giardia duodenalis (11.2%) and Ascaris lumbricoides (8.3%). The presence of intestinal parasites among food handlers was associated with low monthly income (AOR: 2.83, 95% CI 1.50 to 8.84), untrimmed fingernails (AOR: 4.36, 95% CI 1.98 to 11.90), no food safety training (AOR: 2.51, 95% CI 1.20 to 5.58), low level of education (AOR: 3.13, 95% CI 1.34 to 7.44), poor handwashing practice (AOR: 2.16, 95% CI 1.03 to 4.22) and lack of medical check-up (AOR: 2.31, 95% CI 1.18 to 6.95).Conclusion The prevalence of intestinal parasites among food handlers in food establishments in the Lideta subcity of Addis Ababa was high. The presence of intestinal parasites was linked to socioeconomic conditions, poor hand hygiene conditions and absence of food safety training. It is crucially important to promote handwashing practices and provide food hygiene and safety training in these settings.